Biomass derived beta-cyclodextrin-SO3H as a solid acid catalyst for esterification of carboxylic acids with alcohols - Thombal, Raju S.; Jadhav, Amol R.; Jadhav, Vrushali H. (RSC Advances, 2015)
A novel beta-cyclodextrin-SO3H carbon based solid acid catalyst was prepared in a convenient and ecofriendly manner and was characterized using FTIR, PXRD, EDAX and NH3TPD to illustrate that the carbon material has been functionalized with -SO3H, -COOH and -OH groups. The catalyst was studied for esterification of various carboxylic acids and alcohols under solvent free conditions and showed excellent catalytic performance and gave good yields of esters in the range 78-99% at 70 degrees C. No solvent was used either for catalyst preparation nor for esterification reaction. The catalyst can be easily recovered by simple filtration and reused for subsequent three runs without any significant impact on yields of products. The main advantage of this methodology is easy and ecofriendly catalyst preparation, easy catalyst separation, practical simplicity, safe reaction conditions, recyclable catalyst and high product yields.

Synthesis of (+/-) debenzoyl analogs of norsampsones as potential anticancer agents - Jadhav, Amol R.; Thombal, Raju S.; Nigam, Preeti; Jadhav, Vrushali H. (Tetrahedron Letters, 2015)
Synthesis of (+/-) debenzoyl analogs of norsampsones 1 and 2 is reported starting from commercially available 1,3-cyclohexadione in six steps with overall yields of 37% and 36%, respectively. Compounds 1 and 2 were tested for their anticancer activity and showed moderate anticancer activity against HeLa cell lines. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylphloroglucinols; Anticancer; Debenzoyl; Norsampsones

Total synthesis of the natural product EBC-329 - Thombal, Raju S.; Jadhav, Vrushali H. (Organic & Biomolecular Chemistry, 2015)
The first total synthesis of an anti-leukemic diterpene natural product EBC-329 (1) has been accomplished starting from readily available 6,6-dimethyl-3-oxabicyclo[3.1.0] hexane-2,4-dione (7). An efficient and general approach has been reported for the synthesis of EBC-329 in 13 steps with an overall yield of 10%.

Application of glucose derived magnetic solid acid for etherification of 5-HMF to 5-EMF, dehydration of sorbitol to isosorbide, and esterification of fatty acids - Thombal, Raju S.; Jadhav, Vrushali H. (Tetrahedron Letters, 2016)
In this study, the catalytic activity of Glu-Fe3O4-SO3H was evaluated for three acid catalyzed reactions: etherification of 5-hydroxymethylfurfural (5-HMF) to 5-ethoxymethylfurfural (5-EMF) in ethanol, dehydration of sorbitol to isosorbide, and esterification of fatty acids with good yields and selectivity. Moreover, the catalyst can be easily separated from the reaction with an external magnetic force and reused at least five times without a significant decrease in catalytic activity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: dehydration; Esterification; etherification; Magnetic

Sulfonated graphene oxide as highly efficient catalyst for glycosylation - Thombal, Raju S.; Jadhav, Vrushali H. (Journal of Carbohydrate Chemistry, 2016)
Heterogeneous sulfonated graphene oxide for the first time has been used as a green and efficient catalyst for atom-economic glycosylation of unprotected, unactivated glycosyl donors or 2,3,4,6-tetra-O-acetylglycosyltrichloroacetimidate with various acceptors basically in the absence of solvent. The unprotected, unactivated glycosyl donors afforded mixtures of alpha- and beta-glycosides, while the 2,3,4,6-tetra-O-acetylglycosyltrichloroacetimidate afforded beta-glycosylated products with high yields and selectivity. The main advantages of this methodology are easy catalyst preparation, no need for dry reagents and reaction conditions, easy catalyst separation and recycling, and high product yields.
Keywords: glycol donor; glycosyl acceptor; glycosylation; reusability; Sulfonated graphene oxide